Latest developments on Streptococcus suis: An emerging zoonotic pathogen: Part 2 - Mariela Segura (2018)
First International Workshop on Streptococcus suis, Beijing, China, 12-13 August 2013 This second and final chapter of the report on the First International Workshop on Streptococcus suis follows on from Part 1, published in the April 2014, volume 9, issue 4 of Future Microbiology. S. suis is a swine pathogen and a zoonotic agent afflicting people in close contact with infected pigs or pork meat. Although sporadic cases of human infections had been reported worldwide, deadly S. suis outbreaks emerged in Asia. The severity of the disease underscores the lack of knowledge on the virulence and zoonotic evolution of this human-infecting agent. The pathogenesis of the infection, interactions with host cells and new avenues for treatments were among the topics discussed during the First International Workshop on S. suis (China 2013). © 2014 Future Medicine Ltd.